Abundance of food leads to triple clutching of Eurasian eagle-owls (Bubo bubo) and barn owls (Tyto alba) in captivity in Bulgaria - Rusko Petrov; Alian Valchev; Hristina Klisurova (Biodiversity Data Journal)
Food is one of the most important factors for the reproduction capabilities of every living organism. Many studies have highlighted the significance of prey availability on both brood size and offspring survival. In nature, however, it is very challenging to accurately quantify the food intake of the breeding pair. The primary aim of this study is to investigate the reproductive potential of two species in the order Strigiformes, under optimal environmental conditions and adequate nutrition. In some publications, there is evidence for double and even triple clutching. This study evaluates not only the number of clutches, but also the number of eggs laid, fertilised, hatched and released.